(untitled) (Journal of Social Sciences Review, 2022)
Schools’ culture is a key indicator for schools’ effectiveness and overall activities of the school. Its influence is much more significant at the level of secondary schools that are having the duty for the provision of quality graduates to institutions of higher education and skilled people to the job market. School culture consists of norms, beliefs, principles, rituals and behaviors which designs the rules of thinking, feelings and action inside an educational organization and ultimately influences school performance. Having the significant role of school culture in the background, the study aimed to investigate the school culture at secondary level. The objectives of the study were; to investigate the schools’ culture at secondary level and recommend strategies for the improvement of school culture in secondary schools. The design of the study was quantitative descriptive survey. The population of the study was 162 male heads of secondary schools in District Swat. The researcher selected a sample of 118 heads through simple random sampling, developed a Likert questionnaire, validated it and pilot tested for the determination of its reliability. The data were gathered through self-administered questionnaires from the respondents and analyzed with mean scores, standard deviation and Chi-square test. The study found a positive school culture with clear chalked out visions and missions, heads of the school took initiatives for achieving the vision of schools, teachers themselves prepared the rules for functioning of the schools and the head and teachers had collegiality for achieving schools’ visions. The administration of the schools were ambitious, friendly and supportive for the students, democratic in decision making, resolved the problems of teachers and students and were competent enough to satisfy the needs of the schools, teachers worked for the academic excellence of their students, regularly assessed students’ academic progress, focused on co-curricular activities and observed positive human relationship. It further forwarded recommendations for the improvement of the school culture at secondary level.